Insight towards Khalitya - A Single case study (International Journal of Scientific Research in Science and Technology, 2026)
Hair loss is highly prevalent in India, affecting a large portion of the population, with studies showing rates like 60.3% experiencing hair fall, 50.4% baldness, and around 56.5% hair fall in young adults, with females often showing higher rates for hair fall. Ayurveda explains about management of Khalitya with different approaches Acharya Vaghbhata expalins Khalitya under Kapalagataroga were as Acharya Sushuruta explains Under Kshudrarogas.